Terrestrial venomous animals, the envenomings they cause, and treatment perspectives in the Middle East and North Africa. - Timothy P Jenkins; Shirin Ahmadi; Matyas A Bittenbinder; Trenton K Stewart; Dilber E Akgun; Melissa Hale; Nafiseh N Nasrabadi; Darian S Wolff; Freek J Vonk; Jeroen Kool; Andreas H Laustsen (Public Library of Science (PLoS), 2021)
The Middle East and Northern Africa, collectively known as the MENA region, are inhabited by a plethora of venomous animals that cause up to 420,000 bites and stings each year. To understand the resultant health burden and the key variables affecting it, this review describes the epidemiology of snake, scorpion, and spider envenomings primarily based on heterogenous hospital data in the MENA region and the pathologies associated with their venoms. In addition, we discuss the venom composition and the key medically relevant toxins of these venomous animals, and, finally, the antivenoms that are currently in use to counteract them. Unlike Asia and sub-Saharan Africa, scorpion stings are significantly more common (approximately 350,000 cases/year) than snakebites (approximately 70,000 cases/year) and present the most significant contributor to the overall health burden of envenomings, with spider bites being negligible. However, this review also indicates that there is a substantial lack of high-quality envenoming data available for the MENA region, rendering many of these estimates speculative. Our understanding of the venoms and the toxins they contain is also incomplete, but already presents clear trends. For instance, the majority of snake venoms contain snake venom metalloproteinases, while sodium channel-binding toxins and potassium channel-binding toxins are the scorpion toxins that cause most health-related challenges. There also currently exist a plethora of antivenoms, yet only few are clinically validated, and their high cost and limited availability present a substantial health challenge. Yet, some of the insights presented in this review might help direct future research and policy efforts toward the appropriate prioritization of efforts and aid the development of future therapeutic solutions, such as next-generation antivenoms.